1993
DOI: 10.1017/s0950268800068151
|View full text |Cite
|
Sign up to set email alerts
|

A large outbreak of human salmonellosis traced to a local pig farm

Abstract: An outbreak of Salmonella typhimurium definitive type (DT) 193 affecting 206 persons occurred in July and August 1989 in a small town in northern England. A descriptive study suggested that cold meats including pork from a butcher's shop in the town were vehicles of infection. An analytical study of a cohort attending a function in the town showed a significant association between illness and consumption of cold roast pork supplied by the butcher's shop (P = 0.00000004). S. typhimurium DT 193 with the same ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
44
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 3 publications
(2 reference statements)
3
44
0
Order By: Relevance
“…Epidemiological investigations have shown that poultry, poultry products, pork and raw milk are the most common sources of sporadic outbreaks of human salmonellosis 19,20,32 .…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological investigations have shown that poultry, poultry products, pork and raw milk are the most common sources of sporadic outbreaks of human salmonellosis 19,20,32 .…”
Section: Introductionmentioning
confidence: 99%
“…During the 1990s, the importance of pork as a source of human salmonellosis was increasingly recognized [2][3][4], and several generalized outbreaks implicating pork and pork products as vehicles for Salmonella infection have been described [e.g. [5][6][7][8][9][10]. In the late 1990s, the proportion of human salmonellosis cases attributable to pork and pork products was estimated to be approximately 10 % of all cases in Denmark, 15 % in The Netherlands and 20 % in Germany [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been well established that poultry is a major source of food-poisoning caused by Salmonella [12], pork also contributes to human infections [13,19]. ELISA is a valuable tool to detect infected pigs [14] because it is inexpensive and rapid compared with the bacteriological method.…”
Section: Introductionmentioning
confidence: 99%